Classroom relationships in DADA model school (Didactics for Learning Environments):the sociometric: test and teachers point of view - Germani, Sara (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
This paper presents the sociometric analysis of relationships between students (N = 130) of six classes in a lower secondary school in Rome, which adopts the DADA model (Didattiche per Ambienti Di Apprendimento – Didactics for Learning Environments). The knowledge of relationships between students allows teachers to effectively manage the class and with the sociometric test it is possible to highlight the relational structure of the class, identifying students who are in more marginal situations (rejected or isolated). The aim of the survey is to verify teachers point of view on class relationships and on DADA model, to solicit a reflection on the important school role as a place of socialization and peers interaction and on the possible teaching methods provided by DADA model to promote inclusion. The sociometric analysis has brought to light how some students are rejected and how some subgroups are isolated from the rest of the class. The administration of a teachers (N = 11) questionnaire showed that not all teachers recognize the existing relationships between students, but they recognize the importance of a good classroom climate for learning and socialization and see in the DADA an important innovation to promote inclusion. Teachers demonstrate a great propensity for inclusion, but a new teacher professionalism is needed to guide students in constructive interpersonal relationships to ensure student well-being as a key element for the restart after the crisis due to Covid-19, which has strongly changed the social relations between students.